Partizipative Entscheidungsfindung (PEF) - Patient und Arzt als Team = Shared Decision Making (SDM) - Patient and physician as a team - Bieber, Christiane; Gschwendtner, Kathrin M.; Müller, Nicole; Eich, Wolfgang (Diabetologie und Stoffwechsel, 2019)
The article provides an overview on Shared Decision Making (SDM), which is considered as the ideal form of physician-patient-interaction by many stakeholders of the health care system. SDMis distinguished from other models of physician-patient-interaction such as the paternalistic model and the information model. Besides the degree of acceptance of SDMin the general population and among physicians, barriers for its implementation will be reported. Indications for SDMas well as strategies and support material for its use in individual consultations will be discussed and illustrated by an oncological case study. Effects of SDMfor patients as well as for clinicians will be highlighted. After background information on origins of SDM, its significance with regard to health policy in Germany is discussed.
Gesehen am 18.10.2019